Knowledge mapping concerning applications of nanocomposite hydrogels for drug delivery: A bibliometric and visualized study (2003–2022) - Wang, Hao; Fu, Hongxun; Fu, Yefan; Jiang, Lin; Wang, Liye; Tong, Haibin; Xie, Zuoxu; Huang, Peng; Sun, Meiyan (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Nanocomposite Hydrogels (NHs) are 3D molecular networks formed by physically or covalently crosslinking polymer with nanoparticles or nanostructures, which are particularly suitable for serving as carriers for drug delivery systems. Many articles pertaining to the applications of Nanocomposite Hydrogels for drug delivery have been published, however, the use of bibliometric and visualized analysis in this area remains unstudied. The purpose of this bibliometric study intended to comprehensively analyze the knowledge domain, research hotspots and frontiers associated with the applications of Nanocomposite Hydrogels for drug delivery. Methods: We identified and retrieved the publications concerning the applications of NHs for drug delivery between 2003 and 2022 from Web of Science Core Collection Bibliometric and visualized analysis was utilized in this investigative study. Results: 631 articles meeting the inclusion criteria were identified and retrieved from WoSCC. Among those, 2,233 authors worldwide contributed in the studies, accompanied by an average annual article increase of 24.67%. The articles were co-authored by 764 institutions from 52 countries/regions, and China published the most, followed by Iran and the United States. Five institutions published more than 40 papers, namely Univ Tabriz (n = 79), Tabriz Univ Med Sci (n = 70), Islamic Azad Univ (n = 49), Payame Noor Univ (n = 42) and Texas A&M Univ (n = 41). The articles were published in 198 journals, among which the International Journal of Biological Macromolecules (n = 53) published the most articles, followed by Carbohydrate Polymers (n = 24) and ACS Applied Materials and Interfaces (n = 22). The top three journals most locally cited were Carbohydrate Polymers, Biomaterials and Advanced materials. The most productive author was Namazi H (29 articles), followed by Bardajee G (15 articles) and Zhang J (11 articles) and the researchers who worked closely with other ones usually published more papers. “Doxorubicin,” “antibacterial” and “responsive hydrogels” represent the current research hotspots in this field and “cancer therapy” was a rising research topic in recent years. “(cancer) therapeutics” and “bioadhesive” represent the current research frontiers. Conclusion: This bibliometric and visualized analysis offered an investigative study and comprehensive understanding of publications regarding the applications of Nanocomposite Hydrogels for drug delivery from 2003 to 2022. The outcome of this study would provide insights for researchers in the field of Nanocomposite Hydrogels applications for drug delivery.